Identificational Integration of Second Generation Russians in Estonia - Nimmerfeldt, Gerli (Studies of Transition States and Societies, 2009)
This article takes a look at integration processes of second generation Russian youth in Estonia at identity level which is often referred to as identiﬁcational integration. The focus is set on two dimensions of the identiﬁcational integration: identiﬁcation with one’s own ethnic group and identiﬁcation with the majority group in host country. First the role and place of identity in theoretical approaches to integration processes is explored. The second task of the article is to demonstrate the shortcomings of widespread theories and commonly used research instruments for studying the identiﬁcational integration. For that purpose the hypotheses on identiﬁcational integration that stem from literature and presume that national level belongingness either replaces or replenishes ethnic identity are put on test. The analysis is based on both survey data and follow-up face-to-face interviews conducted with 18-35 year old Russians born in Estonia to parents of whom at least one have migrated to Estonia during Soviet times. Conducted analysis on ethnic identity of Russian youth and their sense of belonging to the majority group reveal a need for an enhanced approach to conceptualising and operationalising the identity level integration processes.